Strategies for Entering the Malaysian Export Market for Processed MSME Products : JEL Classification: F14, F18, M31, L26, O24 - Ajie Dahliani; Muliyadi Hamid; Mujahid Yunus (Newinera Publisher, 2026)
This study aims to analyze the export promotion strategies of packaged food products implemented by micro enterprises (UMK) in Nunukan Regency. The research employed a descriptive qualitative approach with data collected through interviews, field observations, and documentation. The data sources consisted of primary data obtained directly from micro entrepreneurs and technical officials, as well as secondary data from relevant policy documents. The findings reveal that the export promotion strategies applied by UMK comprise four main aspects: (1) export certification and licensing, (2) branding and product packaging enhancement, (3) training and capacity building for UMK actors, and (4) cross-border strategic partnerships. Halal certification, distribution permits from BPOM, and export documents such as the Certificate of Origin serve as the main foundations for facilitating export processes. In the aspect of branding, attractive packaging design, strong brand identity, and alignment with Malaysian consumer preferences have proven to enhance product competitiveness. Training in digital marketing, export regulation comprehension, and packaging design plays a vital role in improving the professionalism of UMK actors. Additionally, partnerships with local Malaysian distributors, participation in international trade exhibitions, and collaboration with the Indonesian Embassy (KBRI) and Trade Attachés have expanded market access and strengthened cross-border business networks. Nevertheless, challenges such as limited access to international marketing networks, high promotion and logistics costs, and complex export regulations remain significant obstacles. Local government efforts through certification facilitation, integrated training, and the establishment of trade partnerships have been proven to play a crucial role in strengthening UMK export promotion strategies.